Teaching Medium (2001)
Centro de investigación en la Universidad de Helsinki "Lume Media Centre" por los arqs. <Heikkinen-Komonen>
Keywords: FINLANDIA; HELSINKI; UNIVERSIDADES; CENTROS DE INVESTIGACION; HEIKKINEN, MIKKO; KOMONEN, MARKKU; ARQUITECTURA EDUCACIONAL